Penyelidikan arkeologi di Johor dari sudut pandangan warisan vs pembangunan - Asyaari Muhamad, (Universiti Kebangsaan Malaysia, 2009)
This article focuses on the later history and archaeological heritage of the Malay Johor-Riau-Lingga Sultanate from the 16th to the 19th century CE (Current Era). During this time period, a lot of archaeological research has been done especially by researchers both local and abroad. Some of the areas that will be touched upon in this paper includes Kota Sayong Pinang, Batu Sawar, Kota Seluyut, Kampung Makam, Kota Panchor and Kota Johor Lama. The whole area in question includes the upper reaches of Johor River and streaches down until the lower areas of the Johor River. The supporting evidence for this discussion includes a textual study of several Malay texts (such as Sejarah Melayu, Sejarah Negeri Johor, and Sejarah Petempatan di Sepanjang Sungai Johor) and the archaeological record. This research shows that a lot of the material historical and archaeological evidence is represented by the remains of old forts such as found at Kota Johor Lama, Kota Sayong Pinang, Kota Batu Sawar, Kota Seluyut, the burial sites of the royalty and ruling class, the discovery of gold dinar coins, various weaponary and an overwhelming abudance of ceramics (mostly broken). As much as 211 tombstones of the Aceh style has been identified in the state of Johor. The oldest Acheh tombstone in Johor is dated 1453 CE (or 857 Hijrah according to the Islamic calender) and the finding of ceramics that has been dated between 11 and 14 century CE strongly suggests that there was an earlier kingdom prior to the apperance of the Malay Johor- Riau-Lingga Sultanate. Among the earlier ceramics found include Chinese Song ceramics from the 11 to 13 century CE, Thai ceramics such as Sawankhalok and Sukhothai from the 13 to 15 century CE, Khmer ceramics from the 13 century CE dan Vietnamese ceramics from the 15 century CE. Even so, most of the archaeological evidence along the Johor River has been destroyed as a result of age, current development projects and also the various conflicts during the time of the kingdoms in question